Impact of Poverty and Unemployment in Economic Growth: Case Study of India - Babli (International Journal of Psychosocial Rehabilitation, 2019)
Unemployment rate causes poverty. Poverty affects the growth rate of an economy. Poverty and unemployment are interrelated. Both affect the growth of an economy. Data of the indicators unemployment rate, head count ratio and GDP of India was taken from the official website of the World Bank during the time span 1980-2019. The main objectives of the study are to examine the correlation and impact of poverty and unemployment in economic growth of India. Study also focuses on checking the trends between variables. Correlation and OLS methodology has applied to fulfil the objective of the study. Unemployment rate and head count ratio shows negative low degree of correlation with growth rate. Head count ratio and unemployment rate are positively correlated. 58% of variations in growth rate explained by head count ratio and unemployment rate in India. The GDP of India has fluctuated since 1980. Trends of head count ratio and unemployment rate are decreasing from 1980. The study suggested that the government must increase the usage of proper policies to reduce unemployment and poverty in India.